ESTABLISHMENT OF NATIVE FOREST SPECIES IN RIPARIAN RECOVERY FOREST IN THE PIAUITINGA RIVER, SERGIPE, BRAZIL. - Gama, Dráuzio Correia; Ferreira, Robério Anastácio; Jesus, Janisson Batista de (Floresta, 2020)
The riparian forests of the Piauitinga river Basin, Sergipe state, Brazil, are severely degraded, requiring urgent actions aimed their recovery. In this way, the present work was carried out with the objective of analyzing the establishment of native forest species, implanted in a degraded section of riparian forest of the Piauitinga river, in the municipality of Lagarto state of Sergipe, aiming the forest recovery of this area. It was performed the planting of five native forest species, including pioneers and non-pioneers specie, arranged in a randomized block design, in a total of 200 individuals, distributed in 10 individuals with spacing of 1,5m x 1,5m. The Guazuma ulmifolia Lam. species obtained the best results regarding survival, height (111.94 cm) and diameter at soil height (22.89 mm). Guazuma ulmifolia Lam., Tapirira guianensis Aubl. and Sapindus saponaria L. showed to be able to withstand the adversities of the studied environment, and can be recommended in future projects of recovery of the ciliary forests of that planning unit.